Facile Pd-catalyzed chemoselective transfer hydrogenation of olefins using formic acid in water. Issue 43 (26th October 2016) - Liu, Tianxiang; Zeng, Yongming; Zhang, Hongxi; Wei, Ting; Wu, Xia; Li, Nan
Graphical abstract: Highlights: An effective reduction of olefins in water using formic acid is disclosed. A wide range of saturated hydrocarbons is obtained with remarkable chemoselectivity under mild reaction conditions. The reaction is performed without the use of special equipment or molecular hydrogen gas. Abstract: An effective Pd-catalyzed reduction of olefins in water using formic acid is disclosed. A wide range of saturated hydrocarbons are obtained with an excellent conversion and remarkable chemoselectivity under mild reaction conditions. This protocol is more advantageous and less cumbersome owing to the use of HCOOH as a hydrogen source, water as a solvent, and simple workup procedure.